Thyroid metastasis from small cell lung carcinoma: a case report and review of the literature. (December 2015) - Can, Ahmet; Köksal, Gülistan
Abstract Introduction Small cell lung carcinoma frequently metastasizes to lymph nodes, liver, adrenal glands, bone, brain and pleura. Metastasis of small cell lung cancer to the thyroid gland is extremely rare. Case presentation A 55-year-old Turkish man presented with a mediastinal mass intermingled with mediastinal lymphadenopathy, measuring 11cm in total, and encasing superior vena cava and deviating his trachea, esophagus and vascular structures. He had superior vena cava syndrome. His thyroid appeared normal on computed tomography of his chest. A bronchoscopic biopsy showed small cell lung carcinoma. Chemotherapy with cisplatin and etoposide and external radiotherapy was given. Six months after the presentation, multiple brain metastases were detected on magnetic resonance imaging. Chemotherapy was changed to topotecan and cranial irradiation was performed. At the same time, a right thyroid nodule was detected on computed tomography of his chest and showed growth in size in the following 4 months. A palpable right thyroid nodule came to our attention at that time, the 10th month of presentation. Free thyroxine, free triiodothyronine, thyroid-stimulating hormone, antithyroglobulin and antithyroid peroxidase antibodies were within normal limits. Thyroid ultrasonography showed a right thyroid lobe 26.2×16.8×15.7mm hypoechoic solid nodule with irregular borders. Ultrasonography-guided thyroid fine-needle aspiration biopsy showed metastasis from small cell lung carcinoma. His cranial metastases worsened. He developed right cervical lymph node, hepatic, pancreatic and meningeal metastases and died 15 months after the initial presentation and 9 months after the detection of thyroid metastasis by computed tomography of his chest. Our case and two previously reported cases were male, 55-years old or older and had history of more than 40 pack-years of cigarette smoking. All had metastatic disease elsewhere, when the thyroid metastasis was diagnosed by fine-needle aspiration biopsy. All had poor survival, between 9 and 18 months, after thyroid metastasis was diagnosed. Conclusions We conclude that in a patient with a known history of malignant disease, the finding of a new thyroid mass should be promptly evaluated with a thyroid fine-needle aspiration biopsy to search for metastatic disease. The clinical features of our and two previously reported cases were summarized.